2020
DOI: 10.1097/meg.0000000000001944
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis: risks of postoperative complications with preoperative use of anti-tumor necrosis factor-alpha biologics in inflammatory bowel disease patients

Abstract: PURPOSE Cinnamon has been studied in randomized controlled trials (RCTs) for its glycemic-lowering effects, but studies have been small and show conflicting results. A prior meta-analysis did not show significant results, but several RCTs have been published since then. We conducted an updated systematic review and meta-analysis of RCTs evaluating cinnamon's effect on glycemia and lipid levels. METHODS MEDLINE, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) were searched through February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…The results of previously published meta-analyses reported conflicting findings. Some studies reported a significant increase in overall postoperative complications [ 7 , 8 , 9 , 16 ] or overall infectious postoperative complications [ 3 , 6 , 7 , 9 , 16 ] for anti-TNF-α treated patients, others did not. [ 3 , 5 , 12 , 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of previously published meta-analyses reported conflicting findings. Some studies reported a significant increase in overall postoperative complications [ 7 , 8 , 9 , 16 ] or overall infectious postoperative complications [ 3 , 6 , 7 , 9 , 16 ] for anti-TNF-α treated patients, others did not. [ 3 , 5 , 12 , 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to our knowledge, such extensive subgroup analyses stratified for both the IBD subtype and potential risk factors, were not performed before. [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, recent meta-analyses of published literature suffer from a significant heterogeneity (I2 23–64%) and are contradictory in their conclusions ( 80 ). Three recent reviews conclude that pre-operative anti-TNF therapy is associated with an increased rate of post-operative infectious complications ( 81 83 ), while one did not find such an association ( 84 ). National and international guidelines are also contradictory regarding the management of pre-operative anti-TNF therapy ( 55 , 85 ).…”
Section: Managing Disease-modifying Medicationsmentioning
confidence: 99%